Reproductive and hormonal responses of two breeds of roosters fed diets containing chromium picolinate with or without vitamin C at high ambient temperature - Adebayo, Francis Bosede; Olarotimi, Olumuyiwa Joseph; Adu, Olufemi Adesanya (Acta Scientiarum. Animal Sciences, 2023)
This study evaluated the effects of chromium picolinate (CrPic) with or without vitamin C on the reproductive potentials of cocks raised under high ambient temperature. Four diets contained CrPic at 0.00 to 1.20 mg kg-1 without vitamin C and another four diets contained CrPic with 200 mg vitamin C each. A total of 192 White Leghorn and Noiler cocks (96 cocks each) were randomly assigned to the 8 treatments and replicated 4 times with 6 cocks per replicate in a 2 x2 x 4 factorial experiment. At the end of the sixteen weeks study, twelve birds per treatment were randomly sacrificed. The testes were carefully sampled, weighed and processed for estimation of daily sperm production using the homogenate method. The results revealed that the interactions of 0.40 mg CrPic kg-1 with or without vitamin C significantly (p < 0.05) influenced the gonadal and extra-gonadal weights, semen characteristics among the cocks while the daily sperm production and reproductive hormones were not negatively affected. This study, therefore, concluded that 0.40 mg CrPic kg-1 diet with vitamin C could significantly reduce the effects of heat stress on cocks raised under high ambient temperature without negatively impacting on their normal reproductive functions.